2013
DOI: 10.1002/phar.1175
|View full text |Cite
|
Sign up to set email alerts
|

A Case‐Based Approach to the Practical Application of Dexmedetomidine in Critically Ill Adults

Abstract: Dexmedetomidine is a selective α(2) -adrenoceptor agonist that offers unique sedation because patients are readily awakened while administration continues and the drug does not suppress the respiratory center. Limitations of use include higher acquisition cost, inability to produce deep sedation, and bradycardia and hypotension. Using a case-based approach, the purpose of this review was to qualitatively assess the role of dexmedetomidine in the care of the critically ill and in the management of alcohol withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 83 publications
(307 reference statements)
0
23
0
Order By: Relevance
“…Some studies had been shown that compared to GABA agonists, dexmedetomidine more closely resembles natural non-ReM sleep, which facilitated the patient–caregiver interaction. [14,15] …”
Section: Discussionmentioning
confidence: 99%
“…Some studies had been shown that compared to GABA agonists, dexmedetomidine more closely resembles natural non-ReM sleep, which facilitated the patient–caregiver interaction. [14,15] …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the number of patients in Group D who needed urapidil, phenylephrine, and esmolol was significantly decreased ( P < 0.05). A potential explanation is the better effect of the DEX-opioid combination used in Group D during neurosurgery in terms of sympathetic response and antinociceptive properties, as previous studies have shown that DEX demonstrates nociceptive-modulating effects through both the central and spinal cord α2 receptor without significant respiratory depression (Gil et al, 2009; Goodwin et al, 2013; MacLaren et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…9–12 h, respectively; protein binding, 94 vs. 50%, respectively; and a lipophilic action that is 3.5-fold that of clonidine (Gil et al, 2009). Recent studies have reported that DEX also has many clinical benefits, such as sedation, analgesia, and a low risk of significant respiratory depression (Goodwin et al, 2013; MacLaren et al, 2013). Several studies have shown that DEX can be used safely for 24 h after craniotomy, but the sedative and opioid-sparing effects of an intra- and post-operative infusion of DEX for the first 72 h after neurosurgery have not been reported (Ho, 2012; Shen et al, 2013; Song et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While this is consistent with previous studies comparing dexmedetomidine and benzodiazepines that measured delirium with the Confusion Assessment Method ICU, some of these studies also showed reduced duration of mechanical ventilation which itself may affect the occurrence of delirium. [4][5][6][7] We found less delirium with dexmedetomidine despite similar length of ventilation. These data support minimizing the use of benzodiazepines to reduce the occurrence of delirium.…”
Section: Discussionmentioning
confidence: 71%
“…Other studies suggest that additional sedatives or analgesics may be required to maintain comfort while using dexmedetomidine, possibly because the lighter level of sedation provided by dexmedetomidine may require supplementation when deeper sedation is desired or the lighter level of sedation facilitates the ability of patients to communicate discomfort or request additional sedatives or analgesics. [4][5][6][7] We found the use of open-label midazolam was approximately doubled with dexmedetomidine, but total midazolam exposure was reduced. Less overall benzodiazepine administration should have facilitated extubation.…”
Section: Discussionmentioning
confidence: 91%